Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Minat Beli Ulang di Kafe Kala Kenayan Tulungagung - Yudistira, Bintang Adi; Su'jai, Imam Sukwatus; Suryaningsih, Tutut (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The research began due to the decline in the number of visitors at Kala cafe, so the researcher wanted to investigate the cause of this phenomenon. The researcher found a number of facts obtained from Instagram accounts and maps showing responses from Kala cafe visitors, so the researcher set the focus of the research on product quality, service quality, and repurchase intention. This study aims to investigate the positive impact of service quality and product quality on repurchase intention and to determine the influence of service quality and product quality simultaneously and significantly on repurchase intention. This study applies a quantitative approach with data collection techniques using questionnaires and randomly drawn samples. The research findings show that quality service has a positive and significant influence on repurchase intention, with a regression coefficient value for service quality (X1) of 0.329 and a probability value of 0.000 < a significance level of 0.05. Product quality has a positive and significant impact on repurchase intention with a regression coefficient value of 0.536 and a probability value of 0.000 < a significance level of 0.05. Service quality and product quality are proven to simultaneously influence repurchase intention with a P value of 0.000 < a significance level of 0.05.